Smart Shopping Carts in Food Retailing: Innovative Technology and Shopping Experience in Stationary Retail - Carsten D. Schultz; Patrick Zacheus (Journal of Consumer Behaviour, 2024)
In the development of the Internet of Things, smart shopping carts present a digital innovation that can realize cost-cutting potential and improve the shopping experience. The impact of smart shopping carts on customers' shopping experience is analyzed in stationary grocery retailing. We explore first whether customers are willing to use these technological innovations, specifically smart shopping carts. Second, the effect of smart shopping carts on customers' shopping experiences is evaluated. For this, we employed a mixed method approach combining a survey study and an interview follow-up study. A purposive sampling recruited 291 stationary grocery shoppers. A variance-based structural equation analysis tests the research model for the adoption of smart shopping carts and their relevance to customers' shopping experience. Next, 22 interviews were conducted with grocery shoppers following an intervention approach. Customers are willing to use smart shopping carts when shopping for groceries in stationary retailing. Customers focus on the ease of use and usefulness of the shopping carts, whereas privacy risk and temporary enjoyment are less relevant. However, our empirical results show that affective, social (employee), and physical components predominantly shape the shopping experience compared with the technical component of smart shopping carts. Smart shopping carts similarly affect the cognitive component and the social (customer) component. In contrast to other digital retail innovations, customers seem to value utility of smart shopping carts above else. Stationary retailers can, thus, focus their introduction of smart shopping carts on countering technology anxiety and highlighting customer benefits of shopping comfort and reduced checkout times.
Keywords: 320; customer experience; food retailing; smart shopping carts; technology acceptance